2022
DOI: 10.3389/fmicb.2022.861734
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Suppresses Human Cytomegalovirus-Induced Vascular Endothelial Apoptosis via Rectification of Paradoxical m6A Modification of Mitochondrial Calcium Uniporter mRNA, Which Is Regulated by METTL3 and YTHDF3

Abstract: Human cytomegalovirus (HCMV) infection can induce apoptosis of vascular endothelial cells, which may be the most important element of development and progression of reported atherosclerosis caused by HCMV. As there are no specific drugs to clear HCMV infection, exploration of relevant drugs and mechanisms that can intervene in HCMV-induced atherosclerosis is urgently needed. The present study confirmed that vitamin D3 protected vascular endothelial cells from HCMV-induced apoptosis by inhibiting endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Zhu et al attributed the protective efect of vitamin D3 against atherosclerosis to the hypothesis that human cytomegalovirus infection can trigger vascular endothelial cell apoptosis, which is the most important factor for the development and progression of atherosclerosis, and this vitamin causes inhibition of endoplasmic reticulum and mitochondrial apoptosis pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al attributed the protective efect of vitamin D3 against atherosclerosis to the hypothesis that human cytomegalovirus infection can trigger vascular endothelial cell apoptosis, which is the most important factor for the development and progression of atherosclerosis, and this vitamin causes inhibition of endoplasmic reticulum and mitochondrial apoptosis pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…During the development of human cytomegalovirus-infected atherosclerosis, vitamin D3 can negatively regulate METTL3, inhibit human cytomegalovirus-induced increase in m 6 A methylation of mitochondrial calcium uniporter (MCU) in a YTHDF3-dependent manner, thereby ameliorating cell apoptosis and exerting its endothelial protective function. 133 The latest relevant research demonstrated that exercising training could mediate higher m 6 A levels by down-regulating FTO and reducing myocyte apoptosis, thereby ameliorating myocardial phenotypes in heart failure with preserved ejection fraction. This heralds that FTO acts as a potential therapeutic target for the regulation of cardiomyocyte function.…”
Section: Clinical Application Of M 6 A-pcd Axis In...mentioning
confidence: 99%
“…Elevation of C-C motif chemokine receptor 10 (CCR10) decreases m 6 A methylation, promoting endothelial injury [ 25 ]. Similarly, human cytomegalovirus accelerates endothelial apoptosis through METTL3 and YTHDF3-mediated m 6 A modification [ 26 ]. Kong et al recently identified that m 6 A methylation on TRPC6 enhances hypoxia-mediated EndMT in rat PAECs through activating calcineurin/NFAT signaling [ 27 ].…”
Section: Introductionmentioning
confidence: 99%